(3cJGH aj GdHdGZIs
(3ChdgG (B:s
(3jHOC HGdcdGe Ydi GdeLGR s
(3BNQgG (B:s
(3hGeG dENhGfjGJ bUGMHgG HMSH ENJjGQg hgPG BNQg GdMeO ddg QH GdYGdejf s
(3fbdJ gPg GdfSNI ef fSNI efbhdI ef NW GdeUfa hebQhAI Ydjg hYdjg NWI HGdbQGAI hGdebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs